The impact of mother-infant rooming-in and continuous skin-to-skin contact on newborns - Chu, Huaihui; Ye, Jiqin; Chen, Jie; Dang, Jianhong; Lu, Qiaozhen; Li, Lingling (Frontiers in Pediatrics, 2025)
BackgroundMother-infant skin-to-skin contact (SSC) is a key component of Early Essential Newborn Care (EENC), recommended by the World Health Organization to improve neonatal outcomes. Despite its global adoption, SSC implementation in China remains inconsistent, with limited evidence on its impact in Chinese populations.ObjectiveTo explore the effects of mother-infant rooming-in and continuous SSC on newborn weight, breastfeeding rates, and the use of medications for jaundice.MethodsA total of 2205 women who delivered at Shanghai Changning District Maternal and Child Health Hospital between January and December 2022, including a routine rooming-in care group (1120 cases) and an rooming-in with continuous SSC group (1,085 cases) retrospectively collected from medical records. Both groups of newborns received early essential neonatal care within 90 min of birth, followed by rooming-in with their mothers. Newborns in the routine rooming-in care group received routine rooming-in care, while those in the rooming-in with continuous SSC group were also subjected to continuous SSC with their mothers. The changes in newborn weight, breastfeeding rates, and the use of jaundice medications were compared between the two groups.ResultsThere was no statistically significant difference in the birth weight between the two groups (P > 0.05). The weight loss after birth, comparing 7% and 9% weight loss, was lower in the rooming-in with continuous SSC group than in the routine rooming-in care group (P < 0.05), with a statistically significant difference. The breastfeeding rate in the rooming-in with continuous SSC group was higher than that in the routine rooming-in care group (P < 0.05), showing a statistically significant difference. The use of jaundice medication in the rooming-in with continuous SSC group was lower than in the routine rooming-in care group (P < 0.05), with a statistically significant difference. Multivariate analysis of newborn weight loss greater than 7% revealed that cesarean delivery was a risk factor for excessive weight loss. Multivariate analysis of weight loss greater than 9% indicated that continuous SSC was a protective factor, while mixed feeding was a risk factor. Multivariate analysis of jaundice medication use showed that cesarean delivery and mixed feeding were risk factors, while previous deliveries and SSC were protective factors.ConclusionMother-infant rooming-in with continuous SSC promotes appropriate weight gain in newborns, increases breastfeeding rates, and reduces the need for jaundice medication.